2020
DOI: 10.1017/s0959270920000210
|View full text |Cite
|
Sign up to set email alerts
|

The southern Jiangsu coast is a critical moulting site for Spoon-billed Sandpiper Calidris pygmaea and Nordmann’s Greenshank Tringa guttifer

Abstract: Summary The extent of intertidal flats in the Yellow Sea region has declined significantly in the past few decades, resulting in severe population declines in several waterbird species. The Yellow Sea region holds the primary stopover sites for many shorebirds during their migration to and from northern breeding grounds. However, the functional roles of these sites in shorebirds’ stopover ecology remain poorly understood. Through field surveys between July and November 2015, we investigated the stopover and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…In contrast to regional studies that have reported population declines of migratory birds (Rappole & McDonald 1994, Saino et al 2011, Bairlein 2016, Rosenberg et al 2019, we found that non-migratory birds were more likely to decline globally (Tables 8 and S6). Although migratory birds face unique threats such as habitat loss at stopover sites (Baker et al 2004, Yang et al 2020, their vagility and adoption of new migration routes could enable avoidance of some threats (Dolman & Sutherland 1995). Additionally, we found that non-migratory birds associated with forests or severely fragmented populations were more likely to decline than were non-migrant species without these additional attributes (Tables 8 and S6).…”
Section: Correlation Analysis: Possible Mechanisms Driving Bird Popul...mentioning
confidence: 86%
See 1 more Smart Citation
“…In contrast to regional studies that have reported population declines of migratory birds (Rappole & McDonald 1994, Saino et al 2011, Bairlein 2016, Rosenberg et al 2019, we found that non-migratory birds were more likely to decline globally (Tables 8 and S6). Although migratory birds face unique threats such as habitat loss at stopover sites (Baker et al 2004, Yang et al 2020, their vagility and adoption of new migration routes could enable avoidance of some threats (Dolman & Sutherland 1995). Additionally, we found that non-migratory birds associated with forests or severely fragmented populations were more likely to decline than were non-migrant species without these additional attributes (Tables 8 and S6).…”
Section: Correlation Analysis: Possible Mechanisms Driving Bird Popul...mentioning
confidence: 86%
“…2004, Yang et al . 2020), their vagility and adoption of new migration routes could enable avoidance of some threats (Dolman & Sutherland 1995). Additionally, we found that non‐migratory birds associated with forests or severely fragmented populations were more likely to decline than were non‐migrant species without these additional attributes (Tables 8 and S6).…”
Section: Discussionmentioning
confidence: 99%
“…Many birds in the EAAF, including the endangered species Calidris pygmaea (critically endangered), Calidris tenuirostris, and Platalea minor, stop in the Rudong coastal wetland during their migration (Ma and Chen, 2018;Yang et al, 2020). Thus, the wetland is well-known to birdwatchers worldwide.…”
Section: Methodsmentioning
confidence: 99%
“…1a) (Ma et al, 2006); moreover, some terrestrial birds also rest in these wetlands during their migration (Yong et al, 2015). For threatened species in the yway, such as Calidris pygmaea and Tringa guttifer, these wetlands are crucial for future survival (Peng et al, 2017;Yang et al, 2020). In recent decades, bird surveys have been conducted in some coastal wetlands of East China (Ma et al, 2009;Bai et al, 2015;Peng et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the global importance of wind energy for sustainable development, the negative effects of wind farms on birds need to be taken into consideration [6]. Among the world's eight major migratory waterbird flyways, the East Asian–Australasian flyway (EAAF) supports the highest proportion (19%) of threatened waterbird populations in the world, and is recognised as the most important global waterbird flyway [7]. The EAAF covers a vast region stretching from the Arctic in Siberia and Alaska, southwards through East and South‐East Asia, to Australia and New Zealand.…”
Section: Introductionmentioning
confidence: 99%